Sterilization corrosion inhibitor of polyhexamethylene biguanide inorganic salt, preparation method and application of sterilization corrosion inhibitor in oilfield produced water
By developing the sterilization and corrosion inhibitor of polyhexamethylene biguanide inorganic salts, and using the sustained release characteristics of its compounding system, the serious microbial corrosion problem in the oil field water treatment system has been solved, and effective sterilization and corrosion inhibition effects have been achieved, extending the equipment life and reducing risks.
Patent Information
- Application Number
- CN202510049223.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-13
AI Technical Summary
The microbial corrosion in the oil field water treatment system is severe, resulting in a shortening of the equipment life and increasing economic, environmentally friendly and safety risks. The existing fungicides have drug resistance problems and chemical corrosion risks.
A bactericidal and corrosion inhibitor of polyhexamethylene biguanide inorganic salt was developed. Through the complex system of polyhexamethylene biguanide hydrochloride and zinc sulfate-sodium molybdate, a sustained-release long-acting bactericidal and corrosion inhibitor was formed, which can adsorb the surface of metal materials and slowly release active ingredients, inhibit the formation of bacterial biofilms and effectively kill microorganisms.
This sterilization and corrosion inhibitor can significantly slow down equipment corrosion, extend the working life of the equipment, effectively solve the problems of microbial corrosion and drug resistance, and reduce the risk of chemical corrosion.
Smart Images

Figure CN119896236A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oilfield water treatment, and in particular to a polyhexamethylene biguanide inorganic salt bactericidal corrosion inhibitor for an oilfield water treatment system with high microbial content and severe corrosion, a preparation method and application thereof in oilfield produced water. Background Art
[0002] Corrosion is a kind of material failure behavior that is widely present in the ocean, oil field, and freshwater environment, and its harm is widespread in daily life and almost all industrial industries. According to statistics, the total cost of corrosion in the world is 2.5 trillion US dollars. In my country, the economic losses caused by corrosion each year account for about 5% of the gross national product. Microbial corrosion accounts for about 20% of economic losses. Especially in the field of oil field development, there are many types of microorganisms. The life of metal materials and equipment will be further reduced, and the economic, environmental and safety risks will be greatly increased. It is generally believed that microbial corrosion is closely related to the biofilm formed by microorganisms. Microorganisms tend to grow on the surface of materials and gather together in the form of biofilms to capture nutrients in the environment and provide conditions for growth and metabolism. This makes microorganisms independent of the external environment and less affected by external interference. At the same time, the biofilm attached to the metal surface can also change the physical and chemical properties of the metal surface, promote electrochemical corrosion, and further reduce the service life of the equipment.
[0003] Microbial corrosion in oil fields is mainly caused by bacteria, including sulfate-reducing bacteria (SRB), saprophytic bacteria (TGB), iron bacteria (FB), etc. SRB is an anaerobic bacterium that can oxidize carbon-containing organic compounds or hydrogen and reduce sulfate to produce H2S. It survives in a wide pH range of 5.5-9.0. Sulfate-reducing bacteria commonly found in oil fields are of the genus Desulfonated Bacteria, which mainly attach to the pipe wall in groups or colonies, have a depolarizing effect on the metal surface, accelerate the corrosion of pipelines and equipment, and the corrosion product FeS can block pipelines and injection wells, which is the most harmful to the surface system of oil fields. TGB, also known as slime-forming bacteria, is an aerobic heterotrophic bacterium that secretes a large amount of slime attached to pipelines and equipment, causing biofouling to block injection wells and filters. At the same time, it will also produce an oxygen concentration difference battery, causing corrosion of equipment and pipelines, and provide an environment for sulfate-reducing bacteria to survive and reproduce. FB is a kind of saprophytic fungus with a wide distribution. It mainly oxidizes ferrous iron into high-valent iron and uses the energy released by iron oxidation to meet its survival needs. It is more harmful than general saprophytic fungi and will accelerate the corrosion of equipment and pipelines and cause blockage of injection wells and filters.
[0004] There are many methods for microbial corrosion protection, and chemical methods are one of the simplest and most effective anti-corrosion methods. Fungicides, also known as biocides, bactericides and algaecides, microbicides, etc., are chemical preparations that can effectively control or kill microorganisms in water systems. At present, the fungicides used in oil fields are generally the same as those used for civil water and industrial circulating water. According to their bactericidal mechanism, they can be divided into oxidizing fungicides and non-oxidizing fungicides. Oxidizing fungicides include chlorine, ozone, sodium hypochlorite, chlorine dioxide, etc., which use their strong oxidizing ability to destroy the cell structure of microorganisms or inhibit their metabolic process, but because of their low safety and easy to cause chemical corrosion, they are less used in actual applications. Non-oxidizing fungicides can be divided into aldehydes and ketones, quaternary ammonium salts, quaternary phosphate salts, organic sulfides, and compound types of agents. In recent years, organic guanidine and heterocyclic fungicides have gradually been developed, and have shown good bactericidal effects.
[0005] At present, most oil fields in my country have entered the secondary oil recovery stage. With the increasing water content of produced fluids, the water consumption of water drive is increasing, and microbial corrosion is becoming more common. In order to prevent the injection water from damaging the equipment, pipes and formations, the requirements for produced water reinjection are more stringent, and the demand for fungicides is also increasing. In Jiangsu Oilfield, the water body has a high content of microorganisms and a wide variety of species. Quaternary ammonium salt fungicides were used in the early stage, which led to increased bacterial resistance. The number of sulfate-reducing bacteria, iron bacteria, saprophytes and other bacteria in some water treatment stations reached 10 to the fifth power, which also made the water body deteriorate and brought a large number of corrosion problems. At present, the corrosion rate of some stations has exceeded 0.076 mm / a. Therefore, it is urgent to develop a bactericidal and corrosion inhibitor that kills water microorganisms and inhibits corrosion to ensure the safe operation of oilfield injection and production. Summary of the invention
[0006] Aiming at the problem that microbial corrosion in oilfield water treatment systems in the prior art is becoming more and more serious and the requirements for bactericides are becoming increasingly higher, the present invention provides a bactericidal corrosion inhibitor of polyhexamethylene biguanide inorganic salt, a preparation method and application thereof in oilfield produced water, so that when the oilfield water is sterilized, polyhexamethylene biguanide is slowly released in the water treatment system to effectively kill bacteria in the water body, and at the same time the formation of bacterial biofilm is inhibited, thereby greatly alleviating equipment corrosion and extending the service life of the equipment.
[0007] The invention firstly provides a bactericidal corrosion inhibitor of polyhexamethylene biguanide inorganic salt, which is characterized by comprising a composite system of polyhexamethylene biguanide hydrochloride and zinc sulfate-sodium molybdate.
[0008] Furthermore, the mass ratio of the polyhexamethylene biguanide hydrochloride to the zinc sulfate and sodium molybdate composite system is 10:2-6.
[0009] The bactericidal corrosion inhibitor of the present invention uses polyhexamethylene biguanide as a synthetic substrate, and has the advantages of high stability, degradability, low cost, and green environmental protection; the compound system of sodium molybdate and zinc sulfate can not only effectively inhibit corrosion, but also reduce costs. Because the agent has limited water solubility, it is a slow-release long-acting bactericidal corrosion inhibitor, which can be adsorbed on the surface of metal materials, slowly release polyhexamethylene biguanide, inhibit the formation of bacterial biofilms, effectively kill microorganisms in water bodies, and inhibit metal corrosion.
[0010] To further achieve the purpose of the present invention, the present invention also provides a method for preparing the bactericidal corrosion inhibitor of the above-mentioned polyhexamethylene biguanide inorganic salt, characterized in that the polyhexamethylene biguanide hydrochloride aqueous solution is mixed with an aqueous solution of a composite system of zinc sulfate and sodium molybdate, and then the mixed solution is decanted to remove water, and the precipitate is washed with deionized water and vacuum dried, and finally the dried product is ground into a fine powder to obtain the polyhexamethylene biguanide-inorganic salt.
[0011] Furthermore, the concentration of the polyhexamethylene biguanide hydrochloride aqueous solution is 60-100 g / L.
[0012] Furthermore, the concentration of the aqueous solution of the zinc sulfate-sodium molybdate composite system is 80-240 g / L, and the mass ratio of zinc sulfate to sodium molybdate is 1:1.5-3.
[0013] Furthermore, the vacuum drying temperature is 75-85° C., and the drying time is more than 24 hours.
[0014] Furthermore, the preparation method of the polyhexamethylene biguanide hydrochloride is as follows: guanidine hydrochloride and 1,6-hexanediamine are dissolved in deionized water respectively and mechanically stirred and mixed, and the mixed solution is heated to evaporate water continuously, and the mixture is stirred at a constant temperature for 3 to 4 hours when the temperature is raised to 100 to 120°C, and then the temperature is raised to 160 to 180°C for 3 to 6 hours to obtain a solid phase, and then distilled water is added to the solid phase until it is completely dissolved, and then a saturated sodium chloride aqueous solution is added to the dissolved solution to filter and precipitate, the supernatant is removed by centrifugation, and the solid phase is vacuum dried at 75 to 85°C for more than 24 hours to obtain polyhexamethylene biguanide hydrochloride.
[0015] As a preferred method for preparing the polyhexamethylene biguanide hydrochloride, the weight ratio of guanidine hydrochloride to 1,6-hexanediamine is 1:1-3; More preferably, the weight ratio of guanidine hydrochloride to 1,6-hexanediamine is 1:1.1-1.5.
[0016] The invention discloses a method for preparing a bactericidal corrosion inhibitor of a polyhexamethylene biguanide inorganic salt, wherein guanidine hydrochloride and 1,6-hexamethylenediamine are reacted to generate polyhexamethylene biguanide hydrochloride, and then the polyhexamethylene biguanide inorganic salt is reacted with a composite system of sodium molybdate and zinc sulfate; polyhexamethylene biguanide is used as a synthetic substrate, and has the advantages of high stability, degradability, low cost, and green environmental protection; the composite system of sodium molybdate and zinc sulfate can not only effectively inhibit corrosion, but also reduce costs. The agent has limited water solubility, is a slow-release long-acting bactericidal corrosion inhibitor, can be adsorbed on the surface of metal materials, slowly releases polyhexamethylene biguanide, inhibits the formation of bacterial biofilms, effectively kills microorganisms in water bodies, and inhibits metal corrosion.
[0017] The third purpose of the present invention is to use the above-mentioned polyhexamethylene biguanide inorganic salt bactericidal corrosion inhibitor in an oilfield water treatment system. It is mainly used in the ground treatment system of produced water or the reinjection oil pipe or the oil casing annulus water system. Through regular quantitative addition during the production operation, it gradually dissolves into the output fluid and plays a protective role on the downhole pipe column and the ground pipeline. The particle size of the agent can be adjusted according to factors such as the bottom hole temperature, the flow rate of the fluid, the corrosiveness of the fluid and the required dosing concentration, so as to control the release rate of the agent and obtain the best protection effect and protection period. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 FT-IR charts of the polyhexamethylene biguanide inorganic salt and polyhexamethylene biguanide hydrochloride prepared in Example 1.
[0019] Figure 2 The N80 coupons are corrosion phenomenon diagrams of Comparative Example 1 and Example 1. Among them, Figure (a) is the morphology of the coupon after corrosion in Comparative Example 1, and (b) is the pitting corrosion 3D diagram of the coupon after corrosion in Comparative Example 1; Figure (c) is the morphology of the coupon after corrosion in Example 1, and (d) is the pitting corrosion 3D diagram of the coupon after corrosion in Example 1.
[0020] Figure 3 This is a test diagram of the sustained-release performance of the polyhexamethylene biguanide-inorganic salt of the present invention. DETAILED DESCRIPTION
[0021] The present invention will be described in more detail below through specific examples; however, these examples are not intended to limit the scope of the present invention in any way. Example 1
[0022] (1) Weigh 20.0 g of guanidine hydrochloride and 22 g of 1,6-hexanediamine respectively, dissolve them in deionized water and add them to a three-necked flask equipped with a mechanical stirrer. Slowly raise the temperature to evaporate the water continuously. When the temperature reaches 120 °C, maintain the temperature and stir for 4 h. Then, react at 160 °C for 5 h. Add appropriate amount of distilled water until the mixture is completely dissolved. Then, add saturated sodium chloride aqueous solution to filter the precipitate. Centrifuge to remove the supernatant and dry under vacuum at 80 °C for 24 h to obtain polyhexamethylene biguanide hydrochloride solid.
[0023] (2) Dissolve 3.0 g of zinc sulfate and 9.0 g of sodium molybdate in 50 mL of deionized water respectively, and mix the two evenly while stirring to obtain a zinc sulfate-sodium molybdate composite system.
[0024] (3) Take 20 g of the polyhexamethylene biguanide hydrochloride prepared in step (1) and dissolve it in 200 mL of deionized water. Add 100 mL of the zinc sulfate-sodium molybdate composite system prepared in step (2) under mechanical stirring. The resulting reaction solution is decanted to remove the upper layer of water, washed with deionized water three times, vacuum dried at 80°C for 24 h, and ground into fine powder using an agate mortar to obtain polyhexamethylene biguanide-inorganic salt.
[0025] like Figure 1 The FT-IR diagram of this example is shown. Figure 1 It can be seen that the polyhexamethylene biguanide hydrochloride synthesized in step (1) has a wavelength of 3000-3500 cm -1 A broad peak appears at 2930 cm-1, which is mainly derived from the stretching vibration peaks of -NH, -CH2, and -OH. -1 The absorption peaks at 1540 - 1660 cm -1 The strong stretching vibration peak of C=N appears, which shows that polyhexamethylene biguanide hydrochloride was successfully synthesized. Step (2) Polyhexamethylene biguanide-inorganic salt Compared with the infrared spectrum of polyhexamethylene biguanide hydrochloride synthesized in step (1), the difference is mainly reflected in the fingerprint region, at 1090 cm -1 The stretching vibration peak of the S=O bond appears at 830 cm -1 MoO4 appears 2- The corresponding vibration peaks show that the polyhexamethylene biguanide-inorganic salt composite system was successfully prepared. Example 2
[0026] (1) Weigh 20.0 g of guanidine hydrochloride and 30 g of 1,6-hexanediamine, dissolve them in deionized water and add them to a three-necked flask equipped with a mechanical stirrer. Slowly raise the temperature to evaporate the water. When the temperature reaches 100 °C, maintain the temperature and stir for 4 h. Then, react at 180 °C for 3 h. Add appropriate amount of distilled water to dissolve the mixture. Add saturated sodium chloride aqueous solution to filter the precipitate. Remove the supernatant by centrifugation and dry under vacuum at 80 °C for 24 h to obtain polyhexamethylene biguanide hydrochloride solid.
[0027] (2) Dissolve 3.0 g of zinc sulfate and 6.0 g of sodium molybdate in 50 mL of deionized water respectively, and mix the two evenly while stirring to obtain a zinc sulfate-sodium molybdate composite system.
[0028] (3) Take 20 g of the polyhexamethylene biguanide hydrochloride prepared in step (1) and dissolve it in 200 mL of deionized water. Add 100 mL of the zinc sulfate-sodium molybdate composite system prepared in step (2) under mechanical stirring. The resulting reaction solution is decanted to remove the upper layer of water, washed with deionized water three times, vacuum dried at 80°C for 24 h, and ground into fine powder using an agate mortar to obtain polyhexamethylene biguanide-inorganic salt. Example 3
[0029] (1) Weigh 20.0 g of guanidine hydrochloride and 28 g of 1,6-hexanediamine, dissolve them in deionized water and add them to a three-necked flask equipped with a mechanical stirrer. Slowly raise the temperature to evaporate the water. When the temperature reaches 110 °C, maintain the temperature and stir for 4 h. Then, react at 170 °C for 4 h. Add appropriate amount of distilled water to dissolve the mixture. Add saturated sodium chloride aqueous solution to filter the precipitate. Centrifuge to remove the supernatant and dry under vacuum at 75 °C for 24 h to obtain polyhexamethylene biguanide hydrochloride solid.
[0030] (2) Dissolve 3.0 g of zinc sulfate and 7.0 g of sodium molybdate in 50 mL of deionized water respectively, and mix the two evenly while stirring to obtain a zinc sulfate-sodium molybdate composite system.
[0031] (3) Dissolve 20 g of the polyhexamethylene biguanide hydrochloride prepared in step (1) in 200 mL of deionized water, add 100 mL of the zinc sulfate-sodium molybdate composite system prepared in step (2) under mechanical stirring, decant the resulting reaction solution to remove the upper layer of water, wash with deionized water three times, vacuum dry at 85 °C for 24 h, and grind into fine powder using an agate mortar to obtain polyhexamethylene biguanide-inorganic salt. Example 4
[0032] (1) Weigh 20.0 g of guanidine hydrochloride and 40 g of 1,6-hexanediamine, dissolve them in deionized water and add them to a three-necked flask equipped with a mechanical stirrer. Slowly raise the temperature to evaporate the water. When the temperature reaches 110 °C, maintain the temperature and stir for 4 h. Then, react at 160 °C for 6 h. Add appropriate amount of distilled water to dissolve the mixture. Add saturated sodium chloride aqueous solution to filter the precipitate. Centrifuge to remove the supernatant and dry under vacuum at 85 °C for 24 h to obtain polyhexamethylene biguanide hydrochloride solid.
[0033] (2) Dissolve 2.0 g of zinc sulfate and 5.0 g of sodium molybdate in 50 mL of deionized water respectively, and mix the two evenly while stirring to obtain a zinc sulfate-sodium molybdate composite system.
[0034] (3) Dissolve 20 g of the polyhexamethylene biguanide hydrochloride prepared in step (1) in 200 mL of deionized water, add 100 mL of the zinc sulfate-sodium molybdate composite system prepared in step (2) under mechanical stirring, decant the resulting reaction solution to remove the upper layer of water, wash with deionized water three times, vacuum dry at 85 °C for 24 h, and grind into fine powder using an agate mortar to obtain polyhexamethylene biguanide-inorganic salt. Example 5
[0035] (1) Weigh 20.0 g of guanidine hydrochloride and 60 g of 1,6-hexanediamine, dissolve them in deionized water and add them to a three-necked flask equipped with a mechanical stirrer. Slowly raise the temperature to evaporate the water. When the temperature reaches 120 °C, maintain the temperature and stir for 4 h. Then, react at 160 °C for 5 h. Add appropriate amount of distilled water to dissolve the mixture. Add saturated sodium chloride aqueous solution to filter the precipitate. Remove the supernatant by centrifugation. Dry under vacuum at 80 °C for 24 h to obtain polyhexamethylene biguanide hydrochloride solid.
[0036] (2) Dissolve 2.0 g of zinc sulfate and 2.0 g of sodium molybdate in 50 mL of deionized water respectively, and mix the two evenly while stirring to obtain a zinc sulfate-sodium molybdate composite system.
[0037] (3) Take 20 g of the polyhexamethylene biguanide hydrochloride prepared in step (1) and dissolve it in 200 mL of deionized water. Add 100 mL of the zinc sulfate-sodium molybdate composite system prepared in step (2) under mechanical stirring. The resulting reaction solution is decanted to remove the upper layer of water, washed with deionized water three times, vacuum dried at 80°C for 24 h, and ground into fine powder using an agate mortar to obtain polyhexamethylene biguanide-inorganic salt. Example 6
[0038] (1) Weigh 20.0 g of guanidine hydrochloride and 20 g of 1,6-hexanediamine, dissolve them in deionized water and add them to a three-necked flask equipped with a mechanical stirrer. Slowly raise the temperature to evaporate the water. When the temperature reaches 120 °C, maintain the temperature and stir for 4 h. Then, react at 160 °C for 5 h. Add appropriate amount of distilled water to dissolve the mixture. Add saturated sodium chloride aqueous solution to filter the precipitate. Centrifuge to remove the supernatant and dry under vacuum at 75 °C for 24 h to obtain polyhexamethylene biguanide hydrochloride solid.
[0039] (2) Dissolve 3.0 g of zinc sulfate and 9.0 g of sodium molybdate in 50 mL of deionized water respectively, and mix the two evenly while stirring to obtain a zinc sulfate-sodium molybdate composite system.
[0040] (3) 12 g of the polyhexamethylene biguanide hydrochloride prepared in step (1) was dissolved in 200 mL of deionized water, and 100 mL of the zinc sulfate-sodium molybdate composite system prepared in step (2) was added under mechanical stirring. The resulting reaction solution was decanted to remove the upper layer of water, washed with deionized water three times, vacuum dried at 85°C for 24 h, and ground into fine powder using an agate mortar to obtain polyhexamethylene biguanide-inorganic salt.
[0041] Comparative Example 1
[0042] This comparative example is used to compare the bactericidal effect with that of conventional non-oxidizing bactericides.
[0043] Take 1 g of dodecyl dimethyl benzyl ammonium chloride and dissolve it in 100 mL of deionized water to prepare a 10000 mg / L dodecyl dimethyl benzyl ammonium chloride solution. Take a certain amount of dodecyl dimethyl benzyl ammonium chloride solution and add it to the experimental water sample to test its bactericidal performance. The experimental water sample is a fine filtration outlet water sample from a station in Jiangsu Oilfield, and the water sample contains 11000 SRB / mL, 600 TGB / mL, and 600 FB / mL. Comparative Example 2
[0044] This comparative example is used to compare the corrosion inhibition effect with conventional inorganic corrosion inhibitors.
[0045] Take 1 g of sodium molybdate and dissolve it in 100 mL of deionized water to prepare a 10000 mg / L sodium molybdate solution. Take a certain amount of sodium molybdate solution and add it to the experimental water sample to test its corrosion inhibition performance. The experimental water sample is the outlet water sample of the three-phase separator at a site in Jiangsu Oilfield, and the total mineralization of the water sample is 19213 mg / L. Comparative Example 3
[0046] This comparative example is used to compare the corrosion inhibition effect with polyhexamethylene biguanide hydrochloride-zinc chloride.
[0047] (1) Weigh 20.0 g of guanidine hydrochloride and 24 g of 1,6-hexanediamine, dissolve them in deionized water and add them to a three-necked flask equipped with a mechanical stirrer. Slowly raise the temperature to evaporate the water. When the temperature reaches 120 °C, maintain the temperature and stir for 4 h. Then, react at 160 °C for 5 h. Add appropriate amount of distilled water to dissolve the mixture. Add saturated sodium chloride aqueous solution to filter the precipitate. Remove the supernatant by centrifugation. Dry under vacuum at 80 °C for 24 h to obtain a solid of polyhexamethylene biguanide hydrochloride.
[0048] (2) Take 20 g of the polyhexamethylene biguanide hydrochloride prepared in step (1) and dissolve it in 200 mL of deionized water. Add 12 g of zinc chloride under mechanical stirring. The resulting reaction solution is decanted to remove the upper layer of water, washed with deionized water three times, vacuum dried at 80 ° C for 24 h, and ground into fine powder using an agate mortar to obtain polyhexamethylene biguanide-zinc chloride. Comparative Example 4
[0049] This comparative example is used to compare the corrosion inhibition effect with polyhexamethylene biguanide hydrochloride-zinc sulfate.
[0050] (1) Weigh 20.0 g of guanidine hydrochloride and 24 g of 1,6-hexanediamine, dissolve them in deionized water and add them to a three-necked flask equipped with a mechanical stirrer. Slowly raise the temperature to evaporate the water. When the temperature reaches 120 °C, maintain the temperature and stir for 4 h. Then, react at 160 °C for 5 h. Add appropriate amount of distilled water to dissolve the mixture. Add saturated sodium chloride aqueous solution to filter the precipitate. Remove the supernatant by centrifugation. Dry under vacuum at 80 °C for 24 h to obtain a solid of polyhexamethylene biguanide hydrochloride.
[0051] (2) Take 20 g of the polyhexamethylene biguanide hydrochloride prepared in step (1) and dissolve it in 200 mL of deionized water. Add 12 g of zinc sulfate under mechanical stirring. The resulting reaction solution is decanted to remove the upper layer of water, washed with deionized water three times, vacuum dried at 80 ° C for 24 h, and ground into fine powder using an agate mortar to obtain polyhexamethylene biguanide-zinc sulfate. Comparative Example 5
[0052] This comparative example is used to compare the corrosion inhibition effect with polyhexamethylene biguanide hydrochloride-sodium molybdate.
[0053] (1) Weigh 20.0 g of guanidine hydrochloride and 24 g of 1,6-hexanediamine, dissolve them in deionized water and add them to a three-necked flask equipped with a mechanical stirrer. Slowly raise the temperature to evaporate the water. When the temperature reaches 120 °C, maintain the temperature and stir for 4 h. Then, react at 160 °C for 5 h. Add appropriate amount of distilled water to dissolve the mixture. Add saturated sodium chloride aqueous solution to filter the precipitate. Remove the supernatant by centrifugation. Dry under vacuum at 80 °C for 24 h to obtain a solid of polyhexamethylene biguanide hydrochloride.
[0054] (2) Take 20 g of the polyhexamethylene biguanide hydrochloride prepared in step (1) and dissolve it in 200 mL of deionized water. Add 12 g of sodium molybdate under mechanical stirring. The resulting reaction solution is decanted to remove the upper layer of water, washed with deionized water three times, vacuum dried at 80°C for 24 h, and ground into fine powder using an agate mortar to obtain polyhexamethylene biguanide-sodium molybdate. Comparative Example 6
[0055] (1) Weigh 20.0 g of guanidine hydrochloride and 10 g of 1,6-hexanediamine, dissolve them in deionized water and add them to a three-necked flask equipped with a mechanical stirrer. Slowly raise the temperature to evaporate the water. When the temperature reaches 120 °C, maintain the temperature and stir for 4 h. Then, react at 160 °C for 5 h. Add appropriate amount of distilled water to dissolve the mixture. Add saturated sodium chloride aqueous solution to filter the precipitate. Centrifuge to remove the supernatant and dry under vacuum at 80 °C for 24 h to obtain polyhexamethylene biguanide hydrochloride solid.
[0056] (2) Dissolve 1.0 g of zinc sulfate and 9.0 g of sodium molybdate in 50 mL of deionized water respectively, and mix the two evenly while stirring to obtain a zinc sulfate-sodium molybdate composite system.
[0057] (3) Dissolve 12 g of the polyhexamethylene biguanide hydrochloride prepared in step (1) in 200 mL of deionized water, add 100 mL of the zinc sulfate-sodium molybdate composite system prepared in step (2) under mechanical stirring, decant the resulting reaction solution to remove the upper layer of water, wash with deionized water three times, vacuum dry at 80 °C for 24 h, and grind into fine powder using an agate mortar to obtain polyhexamethylene biguanide-inorganic salt. Comparative Example 7
[0058] (1) Weigh 20.0 g of guanidine hydrochloride and 24 g of 1,6-hexanediamine, dissolve them in deionized water and add them to a three-necked flask equipped with a mechanical stirrer. Slowly raise the temperature to evaporate the water. When the temperature reaches 120 °C, maintain the temperature and stir for 4 h. Then, react at 160 °C for 5 h. Add appropriate amount of distilled water to dissolve the mixture. Add saturated sodium chloride aqueous solution to filter the precipitate. Remove the supernatant by centrifugation. Dry under vacuum at 80 °C for 24 h to obtain a solid of polyhexamethylene biguanide hydrochloride.
[0059] (2) Dissolve 3.0 g of zinc sulfate and 12.0 g of sodium molybdate in 50 mL of deionized water respectively, and mix the two evenly while stirring to obtain a zinc sulfate-sodium molybdate composite system.
[0060] (3) Dissolve 12 g of the polyhexamethylene biguanide hydrochloride prepared in step (1) in 200 mL of deionized water, add 100 mL of the zinc sulfate-sodium molybdate composite system prepared in step (2) under mechanical stirring, decant the resulting reaction solution to remove the upper layer of water, wash with deionized water three times, vacuum dry at 80 °C for 24 h, and grind into fine powder using an agate mortar to obtain polyhexamethylene biguanide-inorganic salt. Comparative Example 8
[0061] (1) Weigh 20.0 g of guanidine hydrochloride and 75 g of 1,6-hexanediamine, dissolve them in deionized water and add them to a three-necked flask equipped with a mechanical stirrer. Slowly raise the temperature to evaporate the water. When the temperature reaches 120 °C, maintain the temperature and stir for 4 h. Then, react at 160 °C for 5 h. Add appropriate amount of distilled water to dissolve the mixture. Add saturated sodium chloride aqueous solution to filter the precipitate. Centrifuge to remove the supernatant and dry under vacuum at 80 °C for 24 h to obtain polyhexamethylene biguanide hydrochloride solid.
[0062] (2) Dissolve 0.3 g of zinc sulfate and 0.9 g of sodium molybdate in 5 mL of deionized water respectively, and mix the two evenly while stirring to obtain a zinc sulfate-sodium molybdate composite system.
[0063] (3) Dissolve 12 g of the polyhexamethylene biguanide hydrochloride prepared in step (1) in 200 mL of deionized water, add 10 mL of the zinc sulfate-sodium molybdate composite system prepared in step (2) under mechanical stirring, decant the resulting reaction solution to remove the upper layer of water, wash with deionized water three times, vacuum dry at 80°C for 24 h, and grind into fine powder using an agate mortar to obtain polyhexamethylene biguanide-inorganic salt. 1. Evaluation of bactericidal performance
[0064] Table 1 shows the bactericidal performance test results of Comparative Example 1 and Examples 1-6. The water sample used is the water sample described in Comparative Example 1, and the water sample contains 11000 SRB / mL, 600 TGB / mL, and 600 FB / mL. The bactericidal performance of the bactericides in each comparative example and example was tested using the method of "Q / SHCG 132-2017 Technical Requirements for Bactericides for Oilfield Produced Water Treatment", and the number of bacteria in the raw water was determined by repeated counting of the secondary bacteria by the dilution method, and the three-tube parallel method was used to determine whether the added bactericide can completely kill the bacteria ("+" means bacteria exist, and "-" means no bacteria). It can be seen from Table 1 that at 50 ppm, polyhexamethylene biguanide-inorganic salt has a certain inhibitory effect on TGB and FB, and at 80 ppm, polyhexamethylene biguanide-inorganic salt can kill SRB, TGB, and FB. At 50 ppm, the bactericidal effect of Examples 1-6 is significantly better than that of each comparative example.
[0065] Table 1 Evaluation of bactericidal performance
[0066] 2. Corrosion inhibition performance evaluation Table 2 is the corrosion inhibition test results of Comparative Examples 2-5, Examples 1, 3, and 4. The water sample used is the water sample described in Comparative Example 2, the water sample mineralization is 19213 mg / L, the water type is calcium chloride type, containing 5867 mg / L sodium ions, 1252 mg / L calcium ions, 99 mg / L magnesium ions, 67 mg / L barium ions, 10989 mg / L chloride ions, 314 mg / L sulfate ions, and 625 mg / L bicarbonate ions. According to the method of "Application and Evaluation of Corrosion Inhibitors in Oil and Gas Fields GB_T 35509-2017", the steel sheet before and after corrosion was analyzed for weight loss and the corrosion rate was calculated. The results are shown in Table 2. It can be seen from Table 2 that the polyhexamethylene biguanide-inorganic salt provided by the present invention has good corrosion inhibition performance and can maintain a corrosion inhibition rate of more than 80% at the temperature of a conventional water treatment system. Compared with Comparative Example 5, the addition of zinc sulfate and the coordinated corrosion inhibition with sodium molybdate both reduce the corrosion rate and reduce the cost. The lowest corrosion rate is 0.011 mm / a, and the corrosion inhibition rate reaches 88.54%, which can meet the anti-corrosion needs of equipment.
[0067] Table 2 serial number Temperature, °C Concentration, ppm Corrosion rate, mm / a Corrosion inhibition rate, % blank 35 0 0.096 0 Comparative Example 2 35 40 0.077 19.79 Comparative Example 3 35 40 0.032 66.67 Comparative Example 4 35 40 0.029 69.80 Comparative Example 5 35 40 0.027 71.88 Comparative Example 6 55 40 0.043 72.08 Comparative Example 7 55 40 0.039 74.68 Example 1 35 40 0.011 88.54 blank 45 0 0.121 0 Example 3 45 40 0.018 85.12 blank 55 0 0.154 0 Example 4 55 40 0.029 81.17 Example 5 55 40 0.038 75.32 Example 6 55 40 0.036 76.62 like Figure 2 The figure shows the corrosion phenomenon of the N80 coupons in Comparative Example 1 and Example 1. The water sample used is the water sample described in Comparative Example 2, and the water sample temperature is 35°C. Figure 2 It can be seen that the surface of the coupon of Example 1 is smoother, and basically no pitting corrosion occurs, with the maximum depth of 0.97 mm. It can be seen that the polyhexamethylene biguanide inorganic salt provided by the present invention has good corrosion inhibition performance and can be adsorbed on the surface of the coupon to effectively prevent equipment corrosion.
[0068] Take 10 mg of polyhexamethylene biguanide inorganic salt and place it in 50 mL of deionized water. Use a UV-visible spectrophotometer at a wavelength of 230 nm to test the concentration of polyhexamethylene biguanide inorganic salt in deionized water at different times. The test results are as follows: Figure 3 As shown in the figure, polyhexamethylene biguanide inorganic salt was released faster in the initial stage and then slowly released over time. After 48 hours, the water concentration reached 84.9 mg / L and the release rate reached 42.7%.
Claims
1. A bactericidal corrosion inhibitor of polyhexamethylene biguanide inorganic salt, characterized in that: The invention comprises a composite system of polyhexamethylene biguanide hydrochloride and zinc sulfate-sodium molybdate.
2. The bactericidal corrosion inhibitor of polyhexamethylene biguanide inorganic salt according to claim 1, characterized in that The mass ratio of the polyhexamethylene biguanide hydrochloride to the zinc sulfate and sodium molybdate composite system is 10:2-6.
3. The method for preparing a bactericidal corrosion inhibitor of polyhexamethylene biguanide inorganic salt according to claim 1 or 2, characterized in that: The polyhexamethylene biguanide hydrochloride aqueous solution is mixed with the aqueous solution of the zinc sulfate and sodium molybdate composite system, and then the mixed solution is decanted to remove water, and the precipitate is washed with deionized water and vacuum dried, and finally the dried product is ground into fine powder to obtain polyhexamethylene biguanide-inorganic salt.
4. The preparation method according to claim 3, characterized in that: The concentration of the polyhexamethylene biguanide hydrochloride aqueous solution is 60-100 g / L.
5. The preparation method according to claim 3, characterized in that: The concentration of the zinc sulfate-sodium molybdate composite system aqueous solution is 80-240 g / L, and the mass ratio of zinc sulfate to sodium molybdate is 1:1.5-3.
6. The preparation method according to claim 3, characterized in that: The vacuum drying temperature is 75-85°C and the drying time is more than 24 hours.
7. The preparation method according to claim 3, characterized in that: The preparation method of the polyhexamethylene biguanide hydrochloride is as follows: guanidine hydrochloride and 1,6-hexanediamine are respectively dissolved in deionized water and mechanically stirred and mixed, and the mixed solution is heated to evaporate water continuously, and the mixture is stirred and reacted at a constant temperature for 3 to 4 hours when the temperature is raised to 100 to 120°C, and then the temperature is raised to a temperature range of 160 to 180°C and reacted for 3 to 6 hours to obtain a solid phase, and then distilled water is added to the solid phase until it is completely dissolved, and then a saturated sodium chloride aqueous solution is added to the dissolved solution to filter and precipitate, and the supernatant is removed by centrifugation, and the solid phase is vacuum dried at 75 to 85°C for more than 24 hours to obtain the polyhexamethylene biguanide hydrochloride.
8. The preparation method according to claim 7, characterized in that: The weight ratio of the guanidine hydrochloride to 1,6-hexanediamine is 1:1-3.
9. The preparation method according to claim 8, characterized in that: The weight ratio of the guanidine hydrochloride to 1,6-hexanediamine is 1:1.1-1.
5.
10. Application of a bactericidal corrosion inhibitor of polyhexamethylene biguanide inorganic salt in an oilfield water treatment system.
Citation Information
Patent Citations
Corrosion inhibition bactericide for oil fields, and preparation method thereof
CN109694702A
Carbon steel corrosion inhibitor containing alkyl guanidine salt and preparation method and application of carbon steel corrosion inhibitor
CN111778511A
Phosphorus-free corrosion and scale inhibitor and preparation method thereof
CN118954796A
Sterilization and disinfection composition
WO2021227214A1
Bactericidal corrosion inhibitor as well as preparation method therefor and use thereof
WO2023124953A1